math-2011-note4 - 6 Integration (A.4) 6.1 Indefinite...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 6 Integration (A.4) 6.1 Indefinite Integral • Consider a continuous function f ( x ) , where f ( x ) > 0 for all x . • Consider the area under the graph of y = f ( x ) from a certain point a to another point x and denote it by A ( x ; a ) . • What is the derivative of A ( x ; a ) at x > a ? • It is lim h → A ( x + h ; a )- A ( x ; a ) h • A ( x + h ; a )- A ( x ; a ) ≈ f ( x ) · h • Hence, lim h → A ( x + h ; a )- A ( x ; a ) h = f ( x ) . Figure 12: Area under a graph • A function F ( x ) whosederivative is a given function f ( x ) is called an antideriva- tive or the indefinite integral of f ( x ) , and written as F ( x ) = integraldisplay f ( x ) dx . • In the previous example, we have A ( x ; a ) = F ( x )+ C for some constant C . • Here are some examples. • integraltext x n dx = 1 n + 1 x n + 1 + C • integraltext ( f + g ) dx = integraltext fdx + integraltext gdx • integraltext ( f prime · g + f · g prime ) dx = f · g + C 18 Figure 13: Definite integral of a function 6.2 Definite Integral • Consider the area A under the graph of y = f ( x ) from a certain point b to another point c > b . • Pick a point a such that a < b < c . • Then A = A ( c ; a )- A ( b ; a ) or A = F ( c )- F ( b ) . • We define the definite integral of f ( x ) from b to c to be F ( c )- F ( b ) and write as F ( c )- F ( b ) = integraldisplay c b f ( x ) dx Economic Example: Integration of MC • Consider a firm with the following cost curves and a horizontal demand curve. • The profit is maximized at the output level where the marginal revenue ( = p ) equals the marginal cost. • The shaded area S can be written as S = pq *- integraltext q * MC ( q ) dq = pq *- TVC ( q * ) , because integraltext q * MC ( q ) dq = C ( q * )- C ( ) = TVC ( q * ) ....
View Full Document

Page1 / 8

math-2011-note4 - 6 Integration (A.4) 6.1 Indefinite...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online